2013
DOI: 10.1088/2041-8205/763/1/l21
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Electron Beams in the Sun's Corona With Radio Dynamic Imaging Spectroscopy

Abstract: We report observations of type III radio bursts at decimeter wavelengths (type IIIdm bursts) -signatures of suprathermal electron beams propagating in the low corona -using the new technique of radio dynamic imaging spectroscopy provided by the recently upgraded Karl G. Jansky Very Large Array (VLA). For the first time, type IIIdm bursts were imaged with high time and frequency resolution over a broad frequency band, allowing electron beam trajectories in the corona to be deduced. Together with simultaneous ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 36 publications
6
98
0
Order By: Relevance
“…Even in this case, it is likely to be only the harmonic component which may be observed (Chen et al, 2013a). Higher background densities increases the collisional rate and reduces the Langmuir wave growth rate.…”
Section: Reverse and Bi-directional Type III Burstsmentioning
confidence: 89%
“…Even in this case, it is likely to be only the harmonic component which may be observed (Chen et al, 2013a). Higher background densities increases the collisional rate and reduces the Langmuir wave growth rate.…”
Section: Reverse and Bi-directional Type III Burstsmentioning
confidence: 89%
“…Recent Solar TErrestrial RElations Observatory observations have also revealed trains of plasma blobs within jets in the closed-field corona near active regions (Zhang et al 2016). Using a new imaging technique, Chen et al (2013) analyzed the moving sources of type III radio bursts in an active-region jet. They found multiple reconnection sites within the jet region and filamentary structures in the jet outflow.…”
Section: Introductionmentioning
confidence: 99%
“…Jets that are correlated with type III bursts accompany flaring activity that ranges from weak transient brightenings and subflares (Kundu et al 1995b;Raulin et al 1996;Nitta et al 2008) to M-class flares (Krucker et al 2011;Chen et al 2013a). Their dimensions may range from about 10 4 km to more than about 10 5 km.…”
Section: Introductionmentioning
confidence: 99%